2015
DOI: 10.1371/journal.pone.0144897
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Dynamic Profiling of Histone Methylation during Nuclear Transfer-Mediated Porcine Somatic Cell Reprogramming

Abstract: The low full-term developmental efficiency of porcine somatic cell nuclear transfer (SCNT) embryos is mainly attributed to imperfect epigenetic reprogramming in the early embryos. However, dynamic expression patterns of histone methylation involved in epigenetic reprogramming progression during porcine SCNT embryo early development remain to be unknown. In this study, we characterized and compared the expression patterns of multiple histone methylation markers including transcriptionally repressive (H3K9me2, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 40 publications
8
41
0
Order By: Relevance
“…Recently, H3K9me3 and H3K79me3 are identified as two negative reprogramming regulators for generating the induced pluripotent stem cells in mouse [15] and human [16]. Similarly, abnormal histone methylation profiles involving H3K9me2 and H3K9me3 are discovered during porcine early SCNT embryonic development in our previous study [17]. Based on these studies, we hypothesize that abnormal histone methylation leads to the reduction of developmental efficiency of SCNT embryos.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, H3K9me3 and H3K79me3 are identified as two negative reprogramming regulators for generating the induced pluripotent stem cells in mouse [15] and human [16]. Similarly, abnormal histone methylation profiles involving H3K9me2 and H3K9me3 are discovered during porcine early SCNT embryonic development in our previous study [17]. Based on these studies, we hypothesize that abnormal histone methylation leads to the reduction of developmental efficiency of SCNT embryos.…”
Section: Introductionmentioning
confidence: 76%
“…Cao et al found that ZGA of porcine fertilized embryos occurred at the 4cell stage in porcine fertilized embryos and was delayed in SCNT embryos via genome-wide gene expression analysis [42], but, a comprehensive analysis of global epigenetic modification of porcine preimplantation embryos has not previously been conducted. Previous studies characterized and compared dynamic genomewide profiles of 12 kinds of histone methylation modification by IF staining [43], but no studies have been conducted on dynamic mRNA profiling of global epigenetic modification enzymes. In our study, we conducted an overall analysis of the expression profiles of 84 representative chromatin modification enzymes by means of RT² Profiler PCR arrays.…”
Section: Discussionmentioning
confidence: 99%
“…H3K4me3 was confirmed as a barrier for mouse SCNT 4-cell arrest, and the down-regulation of H3K4me3 level by over-expression of the H3K4 demethylase KDM5B could promote mouse 4-cell SCNT embryos development [28]. The ZGA of porcine fertilized embryos occurs at the 4-cell stage and is delayed in SCNT embryos [29], and H3K4me3 levels in porcine 4-cell SCNT embryos were confirmed to be abnormally higher than those in IVF embryos by IF staining [14], but the study on how abnormally high H3K4me3 affects ZGA and the development of porcine SCNT embryos, still has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al characterized and compared global dynamic patterns of 12 different histone methylation modifications during porcine SCNT reprogramming by IF staining [14], but no comprehensive analysis has been performed on dynamic mRNA profiling of global epigenetic modification enzymes during porcine SCNT preimplantation embryo development. A previous study suggested that abnormally high mRNA expression of DNMT1/3A would cause either embryonic apoptosis or incomplete reprogramming in porcine cloned embryos [34], but no analysis of DNMT3B was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation